2019
DOI: 10.3390/nu11102460
|View full text |Cite
|
Sign up to set email alerts
|

Are Circulating Mg2+ Levels Associated with Glucose Tolerance Profiles and Incident Type 2 Diabetes?

Abstract: Magnesium (Mg2+) is an enzyme co-factor that plays a key role in many biochemical reactions, as well as in glucose metabolism. Clinical evidences have demonstrated that depletion of serum Mg2+ increases exponentially with the duration of type 2 diabetes mellitus (T2DM). Diabetes is associated with low Mg2+, and hypomagnesemia is associated with insulin resistance, inflammation, and increased risk for cardiovascular disease. In subjects at high risk of inflammation and insulin resistance, supplementation of Mg2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
1
14
1
Order By: Relevance
“…Some studies showed a statistically significant inverse association between plasma magnesium and total or LDL-cholesterol [95,96], but other studies did not observe any significant association [38,55,57,97]. Moreover, there are numerous publications [53,56,57,98,99], that, in agreement with our results, found statistically significant direct associations between plasma magnesium concentrations and total and/or LDL-cholesterol levels, but they did not emphasize the findings. If confirmed in later studies, these findings may help to explain inconsistent results in some studies analyzing plasma magnesium and cardiovascular risk due to the concomitant increase in the atherogenic LDL-cholesterol, but more research must be done on the potential mechanisms involved.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Some studies showed a statistically significant inverse association between plasma magnesium and total or LDL-cholesterol [95,96], but other studies did not observe any significant association [38,55,57,97]. Moreover, there are numerous publications [53,56,57,98,99], that, in agreement with our results, found statistically significant direct associations between plasma magnesium concentrations and total and/or LDL-cholesterol levels, but they did not emphasize the findings. If confirmed in later studies, these findings may help to explain inconsistent results in some studies analyzing plasma magnesium and cardiovascular risk due to the concomitant increase in the atherogenic LDL-cholesterol, but more research must be done on the potential mechanisms involved.…”
Section: Discussionsupporting
confidence: 48%
“…Several prospective cohort studies have analyzed plasma magnesium concentrations and cardiovascular disease incidence and diabetes risk, and some of them reported inverse associations in a meta-analysis [51]. Although at the cross-sectional level numerous researchers have investigated associations between plasma magnesium concentrations and cardiovascular risk factors including plasma lipids, blood pressure, fasting glucose/diabetes, inflammation markers, among others, the consistency (except for type-2 diabetes), is still low [14,[52][53][54][55][56][57][58]. Therefore, further studies are required on different populations in order to better understand those associations as well as the demographic and lifestyle factors associated with plasma magnesium concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…Significant correlations of Mg with TC (r = 0.154, p < 0.001), HDL-C (r = 0.113, p < 0.01), LDL-C (r = 0.170, p < 0.001), but not with TG (r = 0.01, p = 0.981). Higher Mg concentrations were linked with a lower risk of T2DM (OR = 0.765, 95% CI 0.629–0.932, p < 0.01), including in the non-diabetic subjects who were followed-up for nearly 6 years (HR = 0.790, 95% CI: 0.645–0.967; p = 0.022) [ 62 ]. Esmeralda et al (2021) investigated the link between TC, TG and serum/urinary Mg in T2DM versus healthy counterparts.…”
Section: Resultsmentioning
confidence: 99%
“…Mn has been shown to inhibit glucose-stimulated insulin secretion in β cells ( 21 ), while higher urinary Zn or Pb could increase FPG of Chinese adults ( 22 ). In addition, serum Mg levels have been negatively associated with fasting insulin, and higher copper concentrations could increase the risk of glucose dysregulation during pregnancy ( 23 , 24 ). Our previous study ( 25 ) also found that metals including Mn, Cu, Pb, Zn, and Mg in early pregnancy were prospectively related to later FPG in pregnant women.…”
Section: Introductionmentioning
confidence: 99%